The Status of Nomadic Families in Tuva and Features of Their Adaptation to Contemporary Conditions - Rostovskaya, Tamara K.; Natsak, Organa D.; Delovarova, Leila F. (The New Research of Tuva, 2025)
The article analyzes the issues of adaptation of modern nomadic Tuvan families to the changing socio-economic conditions of life in Tuva. The analysis is based on the results of a sociological survey conducted among representatives of nomadic families in 2025.The changes in the size of the social group of shepherds and reindeer herders in Tuva are examined. During the post-Soviet period, a decline in the number of shepherds as both a social and professional group occurred, which correspondingly reduced the number of nomadic families within the structure of Tuvan society. Special support programs for livestock breeders adopted by the republican authorities helped modify this trend, albeit insignificantly, partly because these programs were not specifically targeted at the needs of families. The absence of state support programs for nomadic families in Tuva is noted.Structural changes occurring within Tuvan nomadic families are shown. Several factors (such as children’s education, financial difficulties) lead to the practice of spouses living separately (with the family’s seasonal camp on the one hand and the village or town on the other). The education system obliges children to live far from their parents’ household, thereby disrupting the continuity of traditional family succession. Parents themselves are inclined to have their children obtain professional education and move to other locations. Problems with access to communication networks and digital technologies also cause difficulties in the existence of nomadic families. All these factors complicate the livelihood of nomadic families.
Keywords: nomadic lifestyle; livestock breeding; shepherd; Tuvan family; nomadic family; Internet access; Tuvans